Exploring the Constraints and Mitigation Measures in the Teaching and Learning of Environmental Education in Selected Teachers’ Colleges in Tanzania - Mashaza, Leatitia Gabriel; Bhalalusesa, Eustella; Nzima, Ibrahimu (Papers in Education and Development, 2024)
This paper explored the constraints and measures needed to address the obstacles to quality teaching and learning of environmental education (EE) in teachers’ colleges. The data were gathered from two teachers’ colleges, one in the Morogoro region and the other in the Coast region. This paper employed a qualitative research approach and a case study design. The information was collected through semi-structured interviews and focus group discussions. The sample size was 34, comprising 14 tutors and 20 teacher trainees. The findings revealed major constraints, including resource shortages, inadequate training, insufficient integration of EE content into the curriculum, and limited knowledge among tutors. Conversely, identified mitigation strategies encompassed ongoing training, outdoor educational activities, increased educational resources, and fostering partnerships among community education stakeholders. These findings underscore the critical role of well-prepared teachers in enhancing the effectiveness of environmental education in Tanzanian primary schools. Keywords: Teacher preparation, Teacher Training, Environmental issues